Description of the Impact of Distance Learning (Pjj) on Time Management and Student Achievement Index of FK Yarsi University Classes of 2020 and 2021 During the Pandemicsh - Denis Dida Fahrezzi; Samsul Mustofa (Junior Medical Journal, 2023)
The government through the Ministry of Education declared the implementation of distance learning where all activities use online media. This policy was issued to prevent the chain of spread of COVID-19. The purpose of this study was to find out whether time management during Distance Learning can affect the Academic Achievement Index of Yarsi University Medical Faculty students Class of 2020 and 2021 during the pandemic. In this research, analytic survey research is used so that the research leads to an explanation of the causal relationship between variables. The research design used in this study was cross sectional. Researchers will observe whether there is a relationship between Distance Learning with time management and grade point average. The 2020 and 2021 Medical Faculty Students show that the majority of respondents have poor time management during distance learning.